Learner’s Perspective in Enhancing Vocabulary Acquisition Through TikTok: An Analysis of the @kampunginggrislccom Account - Salsabila, Audiva Syifa; Rizal, Daviq (IJET (Indonesian Journal of English Teaching), 2025)
This study investigates the effectiveness of TikTok, specifically the @kampunginggrislccom account, in enhancing vocabulary acquisition for English as a Foreign Language (EFL) learners. Vocabulary mastery is essential for language development, and in the digital age, TikTok emerges as a promising platform for language learning. The research emphasises the importance of vocabulary in language acquisition, utilising a quantitative approach to understand learners’ perspectives. Results indicate that the @kampunginggrislccom account is highly effective, particularly for participants aged 18-34. The findings highlight TikTok's potential to replace traditional teaching methods, although challenges such as limited time for learning are identified. This research provides valuable insights into language education in the digital age, encouraging exploration of innovative approaches through social media platforms, particularly TikTok.